Photodegradation of organic dye by zinc oxide microstructures decorated with silver Nanoparticles : Effect of different annealing temperature / Nor Atikah Embong - Embong, Nor Atikah (Faculty Of Applied Sciences, 2017)
In this study, zinc oxide (ZnO) microstructures decorated with AgNPs were synthesized via sol gel method. The resulting ZnO catalyst was characterized by X-ray Diffraction (XRD), Field Effect Electron Microscopy (FESEM) and Electron Dispersive X-ray spectroscopy (EDS). XRD analysis show average crystallite size have an increasing pattern of crystallite size in the range of 79.44 - 103.89 nm for pure ZnO and AgZnO at different annealing temperature. ranging from 500 until 900°C. AgZnO-700°C has a smaller particle size than pure ZnO and other samples. The FESEM results exhibit the morphology AgZnO produced was spherical in shape for annealing temperature of 500 DC and bigger and coarsen particle for AgZnO annealed in 900 Dc. The AgZnO samples were tested for photodegradation of Methylene Blue (MB), under UV light. The parameter affecting the degradation performance had been investigated is the effect of different annealing temperature of AgZnO. The results shows AgZnO at annealing temperature of 700°C is the optimum annealing temperature as it performed higher k value compared to other samples.